PERANCANGAN IKLAN TELEVISI SEBAGAI MEDIA PROMOSI J.SIX CAFE DI PADANG - NOVITA TRIANA, Drs. Syafwandi, M.Sn, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
J. Six Cafe is a cafe located in the city of Padang, Standing on December 22 2012, the building area of 180 m². The origin of the name is taken from the café J.six Jalan Ir. H. Juanda No. 06 Padang, The address is the place J.six cafe itself. J.six cafe has a tagline “Hang style cafe, cafeteria style price”. J. Six cafe've never done before promotional media such as radio, and brochures, but not optimal. Authors interested in making television commercials, on television media campaign to reinforce the message to make it more impact on the target audience.The main concern in the design of this, namely how to design a media campaign television ads as j. Six cafe in the field, in order to inform the presence of J. Six cafe, services, food, drink, and the food is priced by weight, cheap to the target audience through television advertising. Design method used is the SWOT analysis. The advantages of television advertising media is the message it conveys is fast and easy to remember. Television commercials to learn about the process of planning, recording, and editing a series of events (the image), to clarify things realistically depict J.six cafe in a short time.Therefore, the design through the medium of television is expected to attract the attention of the target audience, in order to visit the J. Six cafe. Television advertising is the main medium is chosen to promote J. Six cafe, which is supported by other media is a list of menus, chain flags, pins, stickers, T-shirts, mugs, plates, ashtrays, posters, plates and vouchers.Keywords: Design, Promotion, J. six cafe, TV Ad